Untangling climate signals from autogenic changes in long‐term peatland development. Issue 24 (19th December 2015) - Morris, Paul J.; Baird, Andy J.; Young, Dylan M.; Swindles, Graeme T.
Abstract: Peatlands represent important archives of Holocene paleoclimatic information. However, autogenic processes may disconnect peatland hydrological behavior from climate and overwrite climatic signals in peat records. We use a simulation model of peatland development driven by a range of Holocene climate reconstructions to investigate climate signal preservation in peat records. Simulated water‐table depths and peat decomposition profiles exhibit homeostatic recovery from prescribed changes in rainfall, whereas changes in temperature cause lasting alterations to peatland structure and function. Autogenic ecohydrological feedbacks provide both high‐ and low‐pass filters for climatic information, particularly rainfall. Large‐magnitude climatic changes of an intermediate temporal scale (i.e., multidecadal to centennial) are most readily preserved in our simulated peat records. Simulated decomposition signals are offset from the climatic changes that generate them due to a phenomenon known as secondary decomposition. Our study provides the mechanistic foundations for a framework to separate climatic and autogenic signals in peat records. Key Points: Climate signal preservation in peat determined by both magnitude and rate of climate change Ecohydrological feedbacks in bogs provide high‐ and low‐pass filters for climatic signals Timing of peat humification signals consistently offset from climatic drivers